Epidemiological study on intestinal protozoa Entamoeba histolytica & Giardia lamblia in AL-Batha & AL-Gharraf cities of Thi- Qar governorate - عقرب, بسعاد (University of Thi-Qar Journal of Science, 2010)
The present study aims to find out the epidemiology of parasite Entamoeba histolytica and Giardia lamblia and prevalence rates and their relationship with esx and age in each hand Batha and Gharraf of the province of Thi-Qar . The proportion of total infection protozoal intestinal E.histolytica and G.lamblia in Gharraf (48%) higher than the infection in the Batha area (11.4 %) and no significant differences between infection of both. The proportion of the total parasite infection E.histolytica(24.9 %) higher than the proportion of parasite infection G.lamblia (3.2 %) in each of the both . The results showed a significant difference between infection and infection of children and adults of both sexes , male and females in the Batha area where the infection rate in male children (17.5 %) is lower than the infection in male adults (31.7 %) a well as for infection of female children (12.2 %) less than when the adults infection rate (40.3 %) did not observe these difference between the infection in children and adults in Garraf .